Case Report: Heparin-induced thrombocytopenia following double filtration plasmapheresis in a patient with anti-GAD65 autoimmune encephalitis - Ying Chen; Wanwan Li; Liping Ni; Yufang Mei; Yan Zhou; Wenbin Wan (Frontiers in Cardiovascular Medicine)
Autoimmune encephalitis (AE) is a group of disorders characterized by antibodies targeting neuronal cell surface, intracellular structures and synapse antigens. Treatment for AE involves reducing antibody levels and suppressing immune-mediated inflammation using intravenous immunoglobulin, plasma exchange (PE), and immune-modulating agents. PE is commonly used in autoimmune neurological diseases, but the safety issues of PE are worth continuous attention. This case report describes a 28-year-old patient who was diagnosed with anti-GAD65 AE and underwent treatments including double filtration plasmapheresis (DFPP), steroids, and immunosuppressive agents. However, complications arose when the patient developed thrombosis and was diagnosed with type II heparin-induced thrombocytopenia (HIT). He was treated with an oral anticoagulant and eventually recovered. One month later, follow-up examinations showed no presence of emboli and his epilepsy remained well controlled. There is a risk of HIT, a potentially dangerous adverse reaction to heparin during treatment of PE. The current case highlights the importance of monitoring for HIT during PE and the need for alternative anticoagulants.